Axillary arch: a variation of latissimus dorsi muscle - Mohini M Joshi; Rajendra N Wabale (Wolters Kluwer Medknow Publications, 2013)
The axillary arch of Langer (Axillopectoral muscle) is the most common anatomical variant of the axillary musculature. During the dissection of a 63 year old male cadaver, an unusual muscle band was encountered bilaterally and identified as an axillary arch. We here describe the morphology and relationships of the axillary arch in the light of previous such reports. The knowledge of this muscle variation is important for the clinicians, with regards to its potential to cause significant iatrogenic functional defects. Anatomical variations of the axilla are of relevance to surgeons, neurologist, radiologists and cosmetic surgeons due to the increasing surgical importance of this region during axillary surgery for breast cancer, reconstruction procedures, and axillary bypass operations. It is important that surgeons operating in the axilla be aware of this common anatomic variant.